Urupocidin C: a new marine guanidine alkaloid which selectively kills prostate cancer cells via mitochondria targeting - Dyshlovoy, Sergey A. (Sci Rep, 2020)
New bicyclic guanidine alkaloid, urupocidin C (Ur-C) along with the previously known urupocidin A (Ur-A) were isolated from the rare deep-sea marine sponge Monanchora pulchra, harvested in Northwestern Pacific waters. The unique structure of Ur-C was elucidated using 1D and 2D NMR spectroscopy as well as mass spectra. We discovered a promising selectivity of both alkaloids for human prostate cancer (PCa) cells, including highly drug-resistant lines, compared to non-malignant cells. In cancer cells, marine derived compounds were able to induce G1- and S-cell cycle arrest as well as caspase-mediated cell death. For the first time we have identified mitochondrial targeting as a central mechanism of anticancer action for these and similar molecules. Thus, treatment with the isolated alkaloids resulted in mitochondrial membrane permeabilization consequently leading to the release of cytotoxic mitochondrial proteins to cellular cytoplasm, ROS upregulation, consequent activation of caspase-9 and -3, followed by PARP cleavage, DNA fragmentation, and apoptosis. Moreover, synergistic effects were observed when Ur-A and Ur-C were combined with clinically approved PARP inhibitor olaparib. Finally, these alkaloids exhibited additive effects in combination with docetaxel and androgen receptor inhibitor enzalutamide, both applied in PCa therapy. In conclusion, urupocidin-like compounds are promising lead molecules for the development of new drugs for the treatment of advanced PCa.